Teaching and Learning Methods used by Prophet Muhammad P.B.U.H and their Implementation in Veterinary Anatomy Education - Mohamed, Reda (Universitas Islam Negeri Alauddin Makassar, 2021)
The use of various teaching methods allows the teachers to accommodate the different learning styles of the students and allow the students to be active learners and to understand the subjects better as well as to be motivated to learn more. Prophet Muhammad (P.B.U.H) was the first perfect teacher and instructor, and one of his duties was to teach people the revelations that he received from Allah. He selected the best and most effective brilliant methods of teaching, thus helping the listener to clearly understand and remember the knowledge he taught. The learning-teaching methods of the Prophet Muhammad were extracted from his education activities such as face- to-face lecturer, writing method, question-answer method, teaching by practice, practical lessoning, brainstorming, and drawing to teach the foundations of Islam. Learning-teaching methods and techniques that the Prophet Muhammad (P.B.U.H) used in spreading his mission were proven to be effective and successful by applying them in today’s educational understanding of veterinary anatomy.